O Conselho de Desenvolvimento Econômico Nacional e Trabalho (NEDLAC) da África do Sul, o Conselho Nacional de Assessoramento (NAC) da Índia e o Conselho de Desenvolvimento Econômico e Social (CDES) do Brasil: Novas capacidades estatais para o desenvolvimento na semiperiferia? - Eduardo R. Gomes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– By focusing on the relationship between state and society in countries like Brazil, Russia, India, China and South Africa (BRICS), taken as an example of emerging economies, this paper analyzes the advisory counsel to the Executive from Brazil, South Africa and India as a means of expanding state capacity state interaction with society, eventually providing ideas for policy development in the post-neoliberal context. Overall, it is argued that the different ways were structured and the equally diverse working of the studied advice do vary the potential for expansion of state capacity. Finally, we emphasize the contributions of India and South Africa councils to improve the Brazilian experiences.
Keywords: O20; O29; O43; 330; BRICS; Brazil; India; South Africa; state/society councils; state capacities